Advancing personalized medicine for tuberculosis through the application of immune profiling - Thu, Vo Thuy Anh; Dat, Ly Da; Jayanti, Rannissa Puspita; Trinh, Hoang Kim Tu; Hung, Tran Minh; Cho, Yong-Soon; Long, Nguyen Phuoc; Shin, Jae-Gook (Frontiers in Cellular and Infection Microbiology, 2023)
As an over 9000-year-existing infectious disease whose pathogen was scientifically identified in 1882, the understanding of tuberculosis is a great achievement. However, the suboptimal representative biomarkers have restricted the improvement of diagnosis and treatment strategies. While early and precise diagnosis is the key to eradicating Tuberculosis (TB) overgrowth, conventional methods using culture conversion or sputum smear microscopy have failed to meet the demand, especially in high-epidemic developing countries and during the pandemic-associated social restriction. Therefore, the research and development of new affordable and accessible methods are required. Following the emergence of many high-throughput quantifications studied in TB, immunomics gains advantages by directly targeting responsive immune molecules and significantly simplifying workload. In particular, immune profiling has demonstrated a versatile tool and potentially unlocks many rooms for application in TB management. Herein, we review the current approaches for TB control with regard to immunomics’ potential and limitations. Multiple directions are also proposed to helpfully unleash immunomics’ potential in TB research. Not only revealing representative immune biomarkers to rapidly confirm TB diagnosis. Immune profiles of the patients can be valuable covariates for model-informed precision dosing-based treatment monitoring, prediction of the outcome, and optimal dose prediction of anti-TB drugs.